Peer Sympathy for Bullied Youth: Individual and Classroom Considerations. Issue 3 (1st September 2019) - Waasdorp, Tracy E.; Monopoli, W. John; Horowitz-Johnson, Zephyr; Leff, Stephen S.
Abstract: Sympathetic bystanders are necessary for helping to create a positive antibullying climate. The purpose of the current study is to better understand both individual and classroom factors that are associated with having sympathy for victimized peers. Data come from 1, 051 third through fifth graders, predominantly African American youth from 55 classrooms in 6 urban schools. Hierarchical linear models showed that relational aggression (teacher report) and popularity (peer nomination) were associated with low levels of sympathy (self-report). Low classroom levels of aggression (aggregated peer nominations) and high levels of teacher–student closeness (teacher report) were associated with high levels of sympathy. Cross-level interactions revealed boys in highly aggressive classrooms demonstrate less sympathy than boys in less aggressive classrooms. Further, for relationally aggressive youth, being in a classroom with high levels of teacher–student closeness was associated with greater sympathy for bullied peers as compared with relationally aggressive youth in classrooms with low levels of teacher–student closeness. This study underscores the importance of the broader social context for understanding students' displays of sympathy for victimized youth. This has implications for programming to emphasize positive bystander responses in the context of stronger teacher–student relationships and reduce relational aggression, thereby helping to facilitate safer and more secure classrooms.